SISTEM INFORMASI PEMASARAN BARANG AKSESORIS MOTOR PADA TOKO GEMAH RIPAH MOTOR UNGARAN BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract - "MARKETING INFORMATION SYSTEM OF MOTOR ACCESSORIES SHOP Gemah Ripah Unggaran WEB-BASED MOTOR" is a web-based program that can be accessed via the Internet, providing marketing information goods motorcycle accessories, haraga and online marketing barrage. The purpose of this study is to design a system or system architecture, and configuration tools that are used to implement a web application online sales, as well as the PHP code necessary for the implementation of this application. The results of this study is a draft e-commerce that can help marketing goods more broadly motorcycle accessories. Designing a marketing program is useful when implementing an e-commerce site. E-commerce site was made with the support of content management, in order to facilitate the process of renewing the information on the site.Keyword : Website, E-Comerce, internet, Pre Order.